EXAMINING ECOHYDROLOGICAL APPROACHES TO REDUCE PEAT SMOULDERING POTENTIAL IN BLACK SPRUCE PEATLANDS - Deane, Patrick (My University, 2019)
As wildfires increase in frequency, severity, and areal extent in western Canada’s boreal region, wildfire managers are challenged with maintaining current levels of effectiveness. Review of recent wildfire events have identified a need for an improved understanding of vegetation management as a means to mitigate risk of future fires in the wildland-urban and wildland- industry interfaces. Peatlands cover 21% of the land area in continental western Canada; however, there is a lack of peatland-specific fuel modification strategies. The unique ecohydrological feedbacks that operate in these ecosystems provide an opportunity to implement novel peatland-specific treatments in these areas. This thesis examines the effectiveness of novel peatland-specific fuel modification treatments derived from seismic line analogs in reducing the smouldering potential of near-surface moss and peat. An ecohydrological assessment of seismic lines bisecting bogs revealed that alterations to canopy structure and physical peat properties at the time of seismic line establishment leads to persistent changes to the ecohydrological structure and functioning of these systems, marked by limited regeneration of vegetation, dominance of Sphagnum groundcover, and greater near-surface volumetric water contents. Such traits are desirable in fuel modification strategies and therefore, we incorporated the seismic line framework into conventional fuel reduction approaches to create novel peatland-specific fuel modification treatments, involving alterations to canopy structure (thinning and clearing) and physical peat properties (compression). The short-term effects are compression-induced changes to hydrophysical properties including elevated mean near-surface volumetric water contents. Ecological and hydrological indicators of moss moisture stress suggest long-term effects likely include an expansion of Sphagnum moss ground cover within thinned and cleared areas. Ultimately, both short- and long-term effects contribute to the reduction of smouldering potential in near-surface moss and peat. We propose that these peatland-specific fuel modification treatments be incorporated into current FireSmart fuel strategies to reduce wildfire smouldering risk at the wildland-urban and wildland-industry interfaces.
Keywords: Wildfire; Sphagnum; Peatlands; Smouldering; Fuel Modification; Seismic Line